THE SCALE AND REASONS FOR RESIGNATION FROM EMBRYO COLLECTION IN DONOR HEIFERS AND CULLED COWS - Grzeczka, Arkadiusz; Tul, Oleksandra (Translational Research in Veterinary Science, 2023)
In the practice of embryo transfer in cows, it happens that in a certain percentage of donors, for various reasons, the embryo collection procedure is abandoned. Commercial ET teams rarely report the scale and reasons for this. This phenomenon is not better known in culled cows, which are quite often used as exercise material for students to learn the flushing technique of donor cows. The aim of the study was to present the scale and reasons for resignation from embryo collection in commercially used donor heifers and cows, including cows culled from reproductive reasons. The study summarizes the data collected over the last four years in 205 donor cows subjected to the standard superovulation (SOV) procedure. Of the commercialy females subjected to superovulation – 167 were 14-16 month-old heifers, the remaining 38 were cows, including 11 culled females. All animals had not been previously assessed for suitability for ET. The FSH preparation Pluset (Carlier) was used to induce superovulation. Some donors received progesterone support (PRID-Delta (CEVA Animal Health) during FSH administration. To heat induction 500 μg cloprostenol was used. Females were flushed on day 7 after estrus. Rüsch catheter (Neustadt Aisch model) was used for embryo collection. One day before embryo collection 114 donor cows received i.m. injection of 500 μm cloprostenol (Estrumate). Of the heifers, 24 females (14.4%) were not flushed. The main reasons for resignation from embryo collection were: insufficient reaction to FSH – 13 (7.8%), difficulties in introducing the catheter into the uterus – 9 females (5.4%), insufficient synchronization of the estrus cycle (prolonged estrus, numerous follicles present on the ovary – one heifer [(0.5%]) and edema of the rectal mucosa (effect of long-term manipulation) – one heifer (0.5%). Out of 38 cows, 10 females (26.3 %%) were not flushed. Of the 27 commercially flushed cows, 5 had an insufficient response to hormones (18.5%), and one (3.7%) had inappropriate estrus timing. The situation among fattening cows was more dramatic. In this group, 4 cows (36.3%) were not flushed. Two (18.2%) did not react to FSH. Of the donors who received cloprostenol prior to embryo collection, 6 (4.2%) females had difficulties with cervical penetration. In summary; about 1/6 of heifers and 1/4 of cows did not wash the embryos for various reasons. For similar reasons, 1/3 of the cull cows were not rinsed. In the case of this group of donors, prior selection is necessary.